Design Aesthetic in Visual Communication Effectiveness - Gina Fajri Aulia; Nanang Ganda Prawira (Universitas Muhammadiyah Enrekang, 2024)
This research is entitled Design Aesthetics in the Effectiveness of Visual Communication (Analysis of Event Poster Finder #3 DKV UPI). It is motivated by the need for visual communication in the DKV UPI Dies Natalis event to understand the role of design elements and principles in a poster as a promotional media. Visual communication is a key element in creating effective posters and illustrations, especially when promoting events. This article analyzes the effectiveness of visual communication in the promotional poster design for the 3rd Dies Natalis event